Kehebatan Dan Kesetian Mordekhai Membangun Iman Yang Kokoh Dalam Konteks Ester 10:1-3 - Helma Mesya Cristiani Br Siregar; Kevin Marbun (International Forum of Researchers and Lecturers, 2024)
. In writing this article, Mordecai is often interpreted as a lesson about strong faith, greatness, and belief in divine providence. His actions are seen as an example of standing up for what is right and trusting in God's plan, even in the face of adversity. In a theological context, this research aims to provide an example of the importance of loyalty, greatness, and struggle in building strong faith and maintaining faith, as well as belief in God's faithfulness in the midst of life crises and providing inspiration in strengthening faith and obedience to God in any situation.